2011
DOI: 10.1002/ece3.76
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic covariance structure and its divergence for acoustic mate attraction signals among four cricket species

Abstract: The phenotypic variance–covariance matrix (P) describes the multivariate distribution of a population in phenotypic space, providing direct insight into the appropriateness of measured traits within the context of multicollinearity (i.e., do they describe any significant variance that is independent of other traits), and whether trait covariances restrict the combinations of phenotypes available to selection. Given the importance of P, it is therefore surprising that phenotypic covariances are seldom jointly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 113 publications
2
14
0
Order By: Relevance
“…Provided body size is heritable (Simons & Roff, ), larger sons should experience higher reproductive success than smaller sons because they are more likely to win aggressive contests with rivals, achieving a high dominance status and access to mating territories; larger sons should also have more mating opportunities because females prefer to mate with dominant over subordinate males (Loranger & Bertram, ). Similarly, larger sons should experience higher reproductive success than smaller sons because larger males signal for mates louder and more often, and females find louder mate signals more attractive (Bertram, Fitzsimmons, McAuley, Rundle, & Gorelick, ; Bertram & Rook, ; Pacheco & Bertram, ).…”
Section: Discussionmentioning
confidence: 99%
“…Provided body size is heritable (Simons & Roff, ), larger sons should experience higher reproductive success than smaller sons because they are more likely to win aggressive contests with rivals, achieving a high dominance status and access to mating territories; larger sons should also have more mating opportunities because females prefer to mate with dominant over subordinate males (Loranger & Bertram, ). Similarly, larger sons should experience higher reproductive success than smaller sons because larger males signal for mates louder and more often, and females find louder mate signals more attractive (Bertram, Fitzsimmons, McAuley, Rundle, & Gorelick, ; Bertram & Rook, ; Pacheco & Bertram, ).…”
Section: Discussionmentioning
confidence: 99%
“…Since repeatability sets the upper limit for heritability, a low value of .05 suggests a greater influence of environmental variables on male calling effort. A laboratory study on four species of field crickets found repeatability of calling effort to range between 0.43–0.96 [61]. In contrast, in anurans, a field study on the Gulf Coast toad, Bufo valliceps , estimated across-night repeatability of calling effort to range between 0.05–0.08 for two out of three years [62].…”
Section: Discussionmentioning
confidence: 99%
“…Enhancing time spent calling when carrier frequency is sub-optimal may be an effective compensation strategy to attract females, especially given male G . texensis that spend more time calling also call with higher sound pressure levels (correlation = 0.797; [23]).…”
Section: Discussionmentioning
confidence: 99%